Pengaruh Penerapan Model Pembelajaran Role Play terhadap Keterampilan Sosial Siswa pada Mata Pelajaran PAI di SD Islam Darul Makmur Sungai Rotan Kenagarian Batu Taba - Juni Haira; Jasmienti Jasmienti (ARZUSIN, 2026)
Students’ social skills are an important competence in Islamic Religious Education learning because they support the ability to communicate, cooperate, act responsibly, and apply moral values in daily life. Although social skills have received attention in various studies, research that specifically analyzes the effect of the Role Play learning model on students’ social skills in Islamic Religious Education subjects at the elementary school level remains limited. This study aims to analyze the effect of applying the Role Play learning model on the social skills of fourth-grade students in the Islamic Religious Education subject at SD Islam Darul Makmur Sungai Rotan, Kenagarian Batu Taba. This study used a quantitative approach with a Pre-Experimental One Group Pretest-Posttest Design, involving 25 students selected through saturated sampling (total sampling). Data were collected through a social skills questionnaire, observation, and documentation, and were then analyzed using descriptive statistics, the Shapiro-Wilk normality test, and a Paired Sample t-test with the assistance of IBM SPSS Statistics. The results show that the application of the Role Play learning model has a positive and significant effect on students’ social skills, as indicated by an increase in the mean score from 61.12 in the pretest to 89.68 in the posttest, with a significance value of 0.000 (<0.05). These findings contribute to the development of Islamic Religious Education learning based on active learning and strengthen the application of social learning theory and social constructivism in developing students’ social skills. The conclusion of this study emphasizes the importance of the Role Play learning model as an alternative learning strategy that can support the formation of students’ character and social skills at the elementary school level.